Introducing Biblical theology - Grindheim, Sigurd, 1968- (London Bloomsbury, 2013)
How do the different books of the Christian bible contribute to telling the story of God's salvation in Jesus Christ? How can the diverse and sometimes confusing range of perspectives in the bible join together in one picture? Sigurd Grindheim shows students how this picture can be seen as that of the Triune God, the God who interacts. God makes human beings who enjoy a peaceful relationship with him. This relationship is broken because of sin, but God continues to reach out to human beings through covenants. Human failure to be faithful shows that God needs to intervene in a more direct way. In his son Jesus Christ, he comes to earth and brings reconciliation. Grindheim draws on insights from scholarship and tradition to answer the major questions and presents them in a highly accessible form, using examples, revision questions and charts. This book is written specifically for students at the start of courses in the Bible, Theology and Ministry, and for those searching for a deeper understanding of the theology of the Christian bible.
Includes bibliographical references and indexes.
Keywords: Bible -- Theology; Bible -- Criticism, interpretation, etc